Effect of microwave heating time on the gel properties of chicken myofibrillar proteins and their formation mechanism. (17th May 2022) - Wei, Sumeng; Xu, Yining; Kong, Baohua; Wang, Meijuan; Zhang, Jingming; Liu, Qian; Yang, Yuling
Summary: The present work was conducted to illustrate the mechanism of gel formation of myofibrillar proteins (MPs) under different microwave heating times. The results showed that the denaturation enthalpy (Δ H ) of the MPs significantly decreased when the heating time increased from 3 to 9 s and then completely disappeared as the heating time progressed, indicating that the MPs gradually denatured and subsequently aggregated with increasing heating time, which was further verified by the changes in the secondary structure, electrophoretic bands, and gel properties (e.g., water holding capacity and textural profiles) of the MPs. Microstructural images indicated that the MP gel formed under 12 s had the most compact network, indicating that extended microwave heating time could induce quality deterioration of MP gels. Moreover, the hydrophobic forces, electrostatic forces, and disulphide bonds of the MPs gradually intensified with increasing microwave heating time, suggesting that both non‐covalent and covalent bonds could promote molecular denaturation and subsequent aggregation of MPs. In addition, correlation analysis revealed that the changes in the molecular conformation of MPs induced by different microwave heating times could effectively regulate the formation of MP gels and their related properties. Abstract : Different microwave heating times could effectively regulate the formation of MP gels and their related properties, which mainly attributed to the changes of molecular conformations of MPs.